Two-dimensional charge transport in molecularly ordered polymer field-effect transistors - D'Innocenzo, Valerio; Luzio, A.; Abdalla, Hassan; Fabiano, S.; Loi, M. A.; Natali, D.; Petrozza, A.; Kemerink, Martijn; Caironi, M. (Journal of materials chemistry. C, Materials for optical and electronic devices, 2016)
Nanometer-thick Langmuir-Schäfer monolayers of an electron transporting polymer display charge transport, optical and electro-optical properties that do not depend on the number of layers deposited one above the other. This phenomenon can be rationalized with the micro-structure of the specific multi-layers, which introduces an interlayer hopping penalty confining transport to a neat 2D regime, with a channel not extending beyond a single ∼3 nm thick polymer strand, as confirmed by kinetic Monte Carlo simulations. Such findings are critical to establish a quantitative structure-property nexus in high mobility polymer semiconductors and in the control of charge transport at a molecular scale.
Gesehen am 02.12.2019